Potential Carbon Tax in Indonesia: A Literature Review - SAPUTRA, Komang Adi Kurniawan; DHARMAWAN, Nyoman Ari Surya; KAWISANA, Putu Gede Wisnu Permana; LARASDIPUTRA, Gde Deny (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study is study literature on policy tax carbon in Indonesia based on regulation legislation. The purpose of the study literature is to review a way more profound and structured policy tax carbon in Indonesia that is beneficial for realm academics and practitioners. Theoretical studies This is made based on a collection of statements, theoretical bases, and draft fundamentals about tax carbon in Indonesia. The writer converted and adapted several existing articles and readings by thinking about the author and the situation. The results of the study literature find that Indonesia's carbon exchange has launched the so-called IDXCarbon. However, implementation tax cannot yet be implemented. Carbon tax: No For search acceptance, but for an alternative for the business world To meet net zero emissions. Currently, carbon or carbon tax in Indonesia is Still termed levy carbon because carbon tax Has various shapes, taxation, and nontax. Imposition tax Carbon in Indonesia is regulated in Constitution Number 7 of 2021 Harmonization Regulation Taxation. The regulation became the first for the carbon tax in Indonesia.